2016
DOI: 10.1021/acs.joc.6b00471
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Piperazinones Using Amphoteric Aziridine Aldehyde Dimers and Functionalized Isocyanides

Abstract: We have evaluated a range of functionalized isocyanides in the aziridine aldehyde-driven multicomponent synthesis of piperazinones. High diasteroselectivity for each isocyanide was observed. A theoretical evaluation of the reaction course corroborates the experimental data. Moreover, the reactivity of cis- and trans-configured aziridine aldehyde dimers has been compared. This study further probes the dimer-driven mechanism of cyclization and enables an efficient access to a wide range of chiral piperazinones b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Emerging from the calculations was the finding that syn -addition modes Z -pro­( S ) 2a and E -pro­( R ) 2a , wherein isocyanide addition occurs proximal (i.e., syn to) to the l -proline amide carbonyl oxygen, corresponded to the favored stereofacial modes of addition (Figure ). Notably, this result is consistent with our previous investigations of the disrupted Ugi reaction of l -prolinium ions, , despite the increased complexity of the system and the presence of a proline-amide, rather than a proline-carboxylate, directing group.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Emerging from the calculations was the finding that syn -addition modes Z -pro­( S ) 2a and E -pro­( R ) 2a , wherein isocyanide addition occurs proximal (i.e., syn to) to the l -proline amide carbonyl oxygen, corresponded to the favored stereofacial modes of addition (Figure ). Notably, this result is consistent with our previous investigations of the disrupted Ugi reaction of l -prolinium ions, , despite the increased complexity of the system and the presence of a proline-amide, rather than a proline-carboxylate, directing group.…”
Section: Resultssupporting
confidence: 92%
“…We have previously reported a computational study on the mechanism of the reaction between the aziridine aldehyde dimer (( R )- 1 ), l -proline ( 6 ), and t Bu-isocyanide ( 3 ) to form a chiral piperazinone ( 7 ) (Figure a). , Therein, the computations revealed that the observed high diastereoselectivity originated from transition state assembly Z -pro­( S ) (Figure b), involving a carboxylate directed isocyanide addition to a kinetically favored Z -iminium ion formed between l -proline and an aziridine aldehyde dimer. A distinct nitrilium ion intermediate was not observed, and the concerted asynchronous process of isocyanide addition and carboxylate attack was deduced to be the driving force behind the high diastereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of L-valine produced two different oxomorpholines 203 and 204 and a seven-membered lactone 205, in contrast to D-valine, which gave a mixture of syn-and anti-configured 2-oxomorpholines 207. L-amino acids were used by Yudin A. et al as starting material with isocyanides and aziridine aldehydes for piperazinone synthesis [48][49][50]. Piperazinone products 211 and 212 were obtained in all cases as a single diasteroisomers without formation of linear product (Scheme 54).…”
Section: Scheme 45 Formation Of Nine-membered Lactones Via U-5c-3crmentioning
confidence: 99%
“…Piperazinone products 211 and 212 were obtained in all cases as a single diasteroisomers without formation of linear product (Scheme 54). A detailed analysis through X-ray crystallography and NOESY NMR studies revealed that diastereoselectivity L-amino acids were used by Yudin A. et al as starting material with isocyanides and aziridine aldehydes for piperazinone synthesis [48][49][50]. Piperazinone products 211 and 212 were obtained in all cases as a single diasteroisomers without formation of linear product (Scheme 54).…”
Section: Scheme 45 Formation Of Nine-membered Lactones Via U-5c-3crmentioning
confidence: 99%
“…In the case of the chiral primary amino acid, this transformation was selective for the trans -substituted products 90 while the chiral secondary or protected amino acids afforded cis -products. Besides this, a diverse range of functionalized isocyanides were screened in the disrupted Ugi reaction to obtain chiral piperazinones in high stereoselectivities [78].…”
Section: Aziridinesmentioning
confidence: 99%